ORGANIZATION OF EXPERIMENTAL WORKS ON INCREASING THE EFFICIENCY OF TEACHING BIOLOGICAL CHEMISTRY - Makhammadjonov Tursunboy A’zamjon o’g’li (Galaxy International Interdisciplinary Research Journal, 2023)
It is important to implement pedagogical research works and conduct experimental tests to determine their effectiveness. For this purpose, a number of scientific works on the testing of scientific research works and the analysis of their results were studied and put into practice.